Kinetic description of microwave Raman regime free-electron laser in the presence of helical wiggler and guiding magnetic fields - Mishra, P.K. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
A full dispersion relation obtained for free-electron laser by kinetic approach based on the method of characteristics in the presence of circularly polarized, periodic, static helical wiggler magnetic field and guide magnetic field incorporating the detailed relativistic particle trajectories is reduced to Raman regime approximations. The temporal and spatial growth rates are evaluated in microwave region. A detailed analysis has been done for temporal and spatial growth rates in Raman regime, especially for microwave region. The spatial growth rate is more than that of temporal growth. The results have been compared with available results obtained by other techniques.
Optica Applicata, Vol. 37, 2007, nr 1-2, s. 195-204
Keywords: optyka; free electron laser; kinetic approach; microwave; wiggler; guide magnetic field; Raman regime; temporal; spatial